MENINGKATKAN KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR DENGAN METODE JARILIPAN - Saragih, Eva Margaretha; Sirait, Syahriani (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
The implementation of this community service activity aimed to improve elementary school students' numeracy skills by using the Jarilipan method. This activity was carried out at SDN 010246 Banjar with target of 20 students. The Jarilipan method is applied as an innovative learning approach that integrates visual, interactive and game elements to enrich students' learning experiences in understanding mathematical concepts, especially counting operations. The activity implementation method consisted of 3 stages, namely the preparation, implementation and evaluation stages. The results of the activity showed a significant increase in students' numeracy skills after implementing the Jarilipan method. This makes a positive contribution to elementary school students' understanding and numeracy skills. Therefore, the Jarilipan method is an effective and interesting alternative in learning mathematics at the elementary level. It is hoped that the implications of this research will be a guide for teachers and education stakeholders in developing innovative learning strategies to improve student learning outcomes.